Development of teaching materials with agricultural insight to introduce of agriculture in primary school students - Fadlillah, M.; Rahman, Bohri; Istiq'faroh, Nurul (Intelektual Pustaka Media Utama, 2024)
Agriculture is one of the supports for national food needs, so it must continue to be preserved. Unfortunately, nowadays, the sustainability of agriculture is increasingly worrying. Many young people are no longer interested in becoming farmers or working in the agricultural sector. A solution like this must be immediately sought so that regeneration is maintained. This research aimed to develop teaching materials with agricultural insight to introduce of agriculture in primary school students in Indonesia. The research used the research and development (RD) method. Development was carried out using the Borg and Gall model, including: research and informing collecting, planning, preliminary development, and preliminary field testing and main product revision. The research results indicated that: i) the teaching material that was successfully developed was in the form of a textbook entitled “I love agriculture”. This book contains ten materials on agricultural, and ii) the test results showed that the agriculturaloriented teaching materials are of good quality. From the product eligibility test involving material experts and media experts, the average assessment score was 86.25%, while the average assessment score from students reached 85.25%. This research implied that students could get to know and love agriculture through learning activities at school.